Adding zeolite 'minazel-plus' in feeding Oncorhynchus mykiss (Walbaum) and its influence on morphometrical characteristics - Obradović Saša; Vukašinović Marija; Šekler Milanko; Rajković Miodrag; Kosanović Nada (Veterinarski Glasnik, 2006)
The influence of natural zeolite was analyzed, as a food additive applied in a concentration of 0,8% on morphometrical characteristics and basic production index of Rainbow Trout Oncorhynchus mykiss (Walbaum) breeding. By analyzing the obtained results it is found that the presence of zeolite in the trout food has a positive effect with a statistical significance (p<0,05 ) on all analyzed morphometrical indexes of the fish growth rate, on their final body weight, total body length, body length and height, as well as their growth. Including zeolite in the trout mixture had a stimulative effect on the accomplished results of the basic production index of the condition factor (CF), the coefficient of total growth (CTG) and production index (PI) in comparison with the Co-group of fish that are fed without adding zeolite to food.